Predictors of left ventricular remodelling in patients with dilated cardiomyopathy – a cardiovascular magnetic resonance study. (13th February 2020) - Tayal, Upasana; Wage, Ricardo; Newsome, Simon; Manivarmane, Ramasamy; Izgi, Cemil; Muthumala, Amal; Dungu, Jason N.; Assomull, Ravi; Hatipoglu, Suzan; Halliday, Brian P.; Lota, Amrit S.; Ware, James S.; et al.
Abstract: Aims: There is an important need for better biomarkers to predict left ventricular (LV) remodelling in dilated cardiomyopathy (DCM). We undertook a comprehensive assessment of cardiac structure and myocardial composition to determine predictors of remodelling. Methods and results: Prospective study of patients with recent‐onset DCM with cardiovascular magnetic resonance (CMR) assessment of ventricular structure and function, extracellular volume (T1 mapping), myocardial strain, myocardial scar (late gadolinium enhancement) and contractile reserve (dobutamine stress). Regression analyses were used to evaluate predictors of change in LV ejection fraction (LVEF) over 12 months. We evaluated 56 participants (34 DCM patients, median LVEF 43%; 22 controls). Absolute LV contractile reserve predicted change in LVEF (1% increase associated with 0.4% increase in LVEF at 12 months, P = 0.02). Baseline myocardial strain ( P = 0.39 global longitudinal strain), interstitial myocardial fibrosis ( P = 0.41), replacement myocardial fibrosis ( P = 0.25), and right ventricular contractile reserve ( P = 0.17) were not associated with LV reverse remodelling. There was a poor correlation between contractile reserve and either LV extracellular volume fraction (r = −0.22, P = 0.23) or baseline LVEF (r = 0.07, P = 0.62). Men were more likely to experience adverse LV remodelling ( P = 0.01) but age ( P = 0.88) and disease‐modifying heart failure medication (beta‐blocker, P = 0.28; angiotensin‐converting enzyme inhibitor, P = 0.92) did not predict follow‐up LVEF. Conclusions: Substantial recovery of LV function occurs within 12 months in most patients with recent‐onset DCM. Women had the greatest improvement in LVEF. A low LV contractile reserve measured by dobutamine stress CMR appears to identify patients whose LVEF is less likely to recover.